Blockade of astrocytic activation delays the occurrence of severe hypoxia‐induced seizure and respiratory arrest in mice. Issue 8 (4th December 2019) - Fukushi, Isato; Takeda, Kotaro; Uchiyama, Makoto; Kurita, Yuki; Pokorski, Mieczyslaw; Yokota, Shigefumi; Okazaki, Shuntaro; Horiuchi, Jouji; Mori, Yasuo; Okada, Yasumasa
Abstract: Seizures are induced when subjects are exposed to severe hypoxia. It is followed by ventilatory fall‐off and eventual respiratory arrest, which may underlie the pathophysiology of death in patients with epilepsy and severe respiratory disorders. However, the mechanisms of hypoxia‐induced seizures have not been fully understood. Because astrocytes are involved in various neurological disorders, we aimed to investigate whether astrocytes are operational in seizure generation and respiratory arrest in a severe hypoxic condition. We examined the effects of astrocytic activation blockade on responses of EEG and ventilation to severe hypoxia. Adult mice were divided into two groups; in one group ( n = 24) only vehicle was injected, and in the other group ( n = 24) arundic acid, an inhibitory modulator of astrocytic activation, was administered before initiation of recording. After recording EEG and ventilation by whole body plethysmography in room air, the gas in the recording chamber was switched to 5% oxygen (nitrogen balanced) until a seizure and ventilatory depression occurred, followed by prompt switch back to room air. Severe hypoxia initially increased ventilation, followed by a seizure and ventilatory suppression in all mice examined. Fourteen mice without arundic acid showed respiratory arrest during loading of hypoxia. However, 22 mice pretreated with arundic acid did not suffer from respiratory arrest. Time from the onset of hypoxia to the occurrence of seizures was significantly longer in the group with arundic acid than that in the group without arundic acid. We suggest that blockade of astrocytic activation delays the occurrence of seizures and prevents respiratory arrest. Abstract : Representative recordings in hypoxia loading experiments in two groups of mice, one pretreated with vehicle alone and the other with arundic acid, an inhibitor of astrocytic activation. From top to bottom: oxygen concentration in a chamber (Fo2 ), respiratory flow (whole body plethysmogram, inspiration upward), EEG spectrogram in the mouse with vehicle alone, respiratory flow, and EEG spectrogram in the mouse with arundic acid. The percentage of mice with respiratory arrest was significantly smaller in the arundic acid group as compared to the vehicle group. Time from the start of hypoxia to the occurrence of seizures was significantly longer in the mice with arundic acid than that in the vehicle group. Arundic acid delayed the occurrence of severe hypoxia‐induced seizures and prevented subsequent respiratory arrest.